UTILIZATION OF ACTIVE COMPOUNDS IN TUMERIC (Curcuma longa) AS ANTIOXIDANT HERBAL - Reviana Aulia; Ernah Ernah; Syariful Mubarok (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
Turmeric (Curcuma longa) is a plant that has many benefits. Most people use turmeric as a cooking spice, food coloring, or as traditional medicine. Traditional medicine is needed as an alternative method in medical world. At present, a lot of research has been done to develop the use of turmeric. The active compound in turmeric is diferuloylmethane (1,7-bis (4-hydroxy-3-methoxyphenyl) -1,6-heptadiene-3,5-dione) or often called curcumin. Curcumin is a compound that has many benefits. Curcumin can be used as an antioxidant, anti-inflammatory, antibacterial, and antiobesity. The purpose of this review journal is to discuss several studies related to the potential of the active component in turmeric. This journal discusses the benefits of active compounds in turmeric as an antioxidant, anti-inflammatory, antibacterial, and antiobesity.